Tectonostratigraphic Evolution of the Roebuck Basin and the northeast area of the Northern Carnarvon Basin, North West Shelf, Australia - Chen, Peng (Curtin University, 2018)
This thesis presents a detailed investigation into the tectonostratigraphic evolution of the Roebuck Basin and the northeast area of the North Carnarvon Basin. Analysis of 3D structural and stratigraphic architecture, seismic facies and geomorphology provides new insights into the basin development as well as sediment infill processes, which have advanced the understanding of area and could help guide future hydrocarbon exploration.